EFEKTIFITAS PEMBELAJARAN DARING BAHASA INGGRIS PADA MASA PANDEMI COVID-19 DI UNIVERSITAS TRIATMA MULYA BADUNG - Edy Moeljadi; Gunawan Wibisono; Ni Wayan Mekarini (Journal of Tourism and Interdiciplinary Studies, 2021)
This study aims to determine the effectiveness of online English learning during the Covid-19 pandemic at Triatma Mulya University, Badung. It is hoped that this research can provide an overview of the actual situation regarding the learning process that is carried out using online system. With different learning conditions and situations from face-to-face, whether the objectives of learning English are achieved as desired by educators and students or vice versa. This study uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The data or information obtained by the researcher shows that the process of learning English using the online system is quite effective, although in practice there are obstacles from various reasons. From the existing obstacles, connection orThis study uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The data or information obtained by the researcher shows that the process of learning English using the online system is quite effective, although in practice there are obstacles from various reasons. From the existing obstacles, connection or signal problems are the main problems that often make the learning process disrupted. But even so, lecturers try to anticipate the obstacles that occur by always evaluating learning by asking questions directly or giving assignments to students. From the results of the daily evaluation, UTS, and UAS researchers found that lecturers and students achieved what they wanted to achieve in learning result of the daily evaluation, UTS, UAS. researchers found that lecturers and students achieved what they wanted to achieve in learning.